2019
DOI: 10.1186/s12870-019-2061-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of the sweet leaf herb, Stevia rebaudiana B., cultivated and landraces germplasm assessed by EST-SSRs genotyping and steviol glycosides phenotyping

Abstract: BackgroundStevia rebaudiana (Asteraceae), native from Paraguay, accumulates steviol glycosides (SGs) into its leaves. These compounds exhibit acaloric intense sweet taste which answers to consumer demands for reducing daily sugar intake. Despite the developpement of S. rebaudiana cultivation all over the world, the development of new cultivars is very recent, in particular due to a colossal lack of (1) germplasm collection and breeding, (2) studies on genetic diversity and its structuring, (3) genomic tools.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
14
1
1
Order By: Relevance
“…Likewise, as was observed in our study with ISSR markers, the selection pressure adopted by Carvalho et al (2011) to form crops with characteristics of interest resulted in genetically structured. EST-SSR also revealed higher genetic diversity in landraces than in the cultivated populations ( Cosson et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, as was observed in our study with ISSR markers, the selection pressure adopted by Carvalho et al (2011) to form crops with characteristics of interest resulted in genetically structured. EST-SSR also revealed higher genetic diversity in landraces than in the cultivated populations ( Cosson et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity within each accession or collection has not been revealed by ISSR markers. Molecular polymorphism within landraces and cultivated populations of stevia have been investigated by esterase isozymes and expressed sequence tags (EST) in simple sequence repeats (SSRs) as markers ( Carvalho et al 2011 , Cosson et al 2019 ). Genetic diversity in esterase loci within of S. rebaudiana cultivated populations which were subjected to artificial selection pressure of characteristics such as greater height or early flowering, demonstrated that this procedure leads towards the fixation of different alleles and different esterase phenotype patterns ( Carvalho et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Liposthey field, four genetic resources (Table 1) of different origins studied in Hastoy, Cosson, et al (2019) were chosen. In the Blagon field, four populations from crosses between genetic resources presented in Cosson et al (2019), namely Cult76_GER × Cult35_FRA, Cult102_SPA × Cult35_FRA, Cult36_FRA × Cult103_SPA and Cult34_FRA × Cult36_FRA, were analysed (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…These markers can competently be used in the genotyping process with a good genome sampling, which makes them suitable to estimate genotypes relatedness that requires multilocus genotype identification [ 28 ]. Kaur et al [ 29 ] and Bhandawat et al [ 30 ] were the pioneers in microsatellite markers development and use in S. rebaudiana and, recently, from freely available expressed sequence data (ESTs), and Cosson et al [ 31 ] also developed molecular markers (EST-SSRs) for population genetic and germplasm characterization studies. Recently, also a group of S. rebaudiana genotypes from Paraguay were studied with SSR and ISSR [ 32 ], and analysed as dominant markers.…”
Section: Introductionmentioning
confidence: 99%